Integration of PhET Simulations in Physics Learning Models: A Theoretical Study of Students' Critical Thinking Skills - Qothrunnada, Qothrunnada; Gunawan , Gunawan (Indonesian Journal of STEM Education, 2023)
This study aims to theoretically examine the integration of PhET Interactive Simulations within various physics learning models and its contribution to developing students' critical thinking skills. Through a narrative review of scientific literature from reputable databases, it was found that PhET serves as an effective cognitive instrument that visualizes abstract concepts through real-time variable manipulation. Synthesis results indicate that the synergy between PhET and innovative learning models, such as Problem-Based Learning (PBL) and guided inquiry, significantly stimulates critical thinking indicators, including analysis, evaluation, and inference. The use of this virtual laboratory not only enhances conceptual understanding but also provides a safe explorative environment for students. This study concludes that the structured integration of PhET within instructional design is a crucial strategy for strengthening higher-order thinking skills in modern science education.